Pengaruh Paket SESASI (Sepekan Edukasi ASI dan MPASI) Terhadap Pengetahuan Kader Di Desa Caturharjo, Kecamatan Pandak, Bantul, DIY - Puspitarini, Zenni; Deny Kristanto, Paulinus (Profesi (Profesional Islam) : Media Publikasi Penelitian, 2021)
The application of lactation counseling in postpartum mothers is still not optimal so that mothers experience difficulties when first contact with their babies and cause a decrease in breastfeeding ability. Lactation counseling on early maternal and infant contact by the ASI Support Group is very important in supporting postpartum mothers to maintain breastfeeding and optimize breastfeeding for newborns. The results of a preliminary study conducted at the Pandak 2 Public Health Center in Bantul, are known to have formed a Mother Support Group, but the Mother Support Groups that have been formed are not yet optimal. The results of the February 2018 survey from the Pandak 2 Puskesmas in Catuharjo Village obtained data on exclusive breastfeeding coverage of 77.94%. This study aims to determine the effectiveness of the SESASI Package (One-week Education Program about ASI and MP-ASI) on increasing the knowledge of cadres / Support Groups for mothers. The design of this study is quasi experimental pretest and postest design. Data was collected in the Working Area of ​​Pandak 2 Public Health Center in Bantul, Caturharjo Village. The sample in this study was a cadre of toddlers and Mother Support Groups. The sampling technique uses cluster sampling. Bivariate analysis using paired t-test. The results showed an increase in the median value of knowledge from 86.5 to 90 and the value of p = 0,000 (p <0.05). The conclusion in this study is an increase in knowledge before and after education.